Clinical influence of calcium hydroxide and N-acetylcysteine on the levels of resolvins E1 and D2 in apical periodontitis - Corazza, B. J.M. [UNESP]; Martinho, F. C.; Khoury, R. D. [UNESP]; Toia, C. C. [UNESP]; Orozco, E. I.F. [UNESP]; Prado, R. F. [UNESP]; Machado, F. P. [UNESP]; Valera, M. C. [UNESP] (Wiley, 2021)
Aim: To investigate the presence of resolvins E1 (RvE1) and D2 (RvD2) in teeth with primary endodontic infections and apical periodontitis, and to assess the influence of calcium hydroxide medication [Ca(OH)2], in association with 2% chlorhexidine gel (2% CHX gel), and N-acetylcysteine (NAC) on the levels of RvE1 and RvD2 in periapical tissues. Methodology: Thirty-six single-rooted teeth with primary endodontic infections and apical periodontitis were selected and randomly divided into three groups according to the medication: [Ca(OH)2] + saline solution (SSL) [Ca(OH)2 + SSL group] (n = 12), Ca(OH)2 + 2% chlorhexidine gel [Ca(OH)2 + 2% CHX gel group] (n = 12) and NAC [NAC group] (n = 12). Samples were collected from the periapical interstitial fluid at two different sampling times: before (S1) and after 14 days of intracanal medications (S2). Resolvins were measured using the enzyme-linked immunosorbent assay. Data were analysed using paired t-test, Wilcoxon test and Kruskal–Wallis test, followed by Dunn’s post hoc test; all statistical tests were performed at a significance level of 5%. Results: RvE1 and RvD2 were detected in 100% of the samples (36/36) at S1 and S2. Ca(OH)2 medication did not increase the levels of RvE1 or RvD2 (both P > 0.05); however, NAC significantly increased the levels of RvE1 and RvD2 after 14 days of treatment (P < 0.05). Conclusions: RvE1 and RvD2 were detected in periapical tissues from teeth with root canal infections. Moreover, calcium hydroxide medication did not increase the levels of resolvins in apical periodontitis. In contrast, the use of NAC intracanal medication significantly increased the levels of RvE1 and RvD2 after 14 days of treatment.
Keywords: calcium hydroxide; intracanal medication; resolvins; root canal